"Everyone was looking at you smiling": East London residents' experiences of the 2012 Olympics and its legacy on the social determinants of health. (November 2015) - Thompson, C.; Lewis, D.J.; Greenhalgh, T.; Smith, N.R.; Fahy, A.E.; Cummins, S.
Abstract: Mega-sporting event regeneration, as a specific approach to urban renewal, uses impending host-city status as a catalyst for revitalisation and has the potential to improve health both through addressing deprivation and by promoting increased sport and physical activity among the host-city's population. This qualitative study explored how hosting of the London 2012 Games impacted upon the way East London residents perceived and experienced the social determinants of health in their local neighbourhood. We conducted narrative family interviews, go-along interviews and video focus group workshops with 66 Newham residents, aged 12–55 years, immediately after the Games. A narrative analytic approach examined accounts of health and wellbeing experiences in terms of neighbourhood change and the spectacle of the Games. Participants of this qualitative study generally welcomed the respite and the unexpected chance to live in a cleaner, safer and more unified environment. However, this positivity was underscored by an acute awareness that this was a very temporary situation and one that was intended to support the event rather than residents. Highlights: The 2012 Olympic bid promised a health and social legacy for local residents. Residents in this deprived locality experienced only temporary respite. The long-term 'regeneration' impact of sporting mega-events remains unproven.